Copyright and Popular Media - Cvetkovski, T. author. aut Link
XXII, 299 p.
Keywords: Copyright governance is in a state of flux because the boundaries between legal and illegal consumption have blurred. Trajce Cvetkovski interrogates the disorganizational effects of piracy and emerging technologies on the political economy of copyright in popular music, film and gaming industries.